Assessment of the flexibility of implementing lean tools. Issue 1 (October 2021) - Pessoa, B; Ferreira, L P; Silva, F J G; Sá, J C; Ávila, P; Ares, J E
Abstract: Lean production has already proved to constitute an effective management philosophy when eliminating time loss in production processes. However, achieving economic results is currently insufficient. In the context of this study, research was conducted on the Web of Science platform in order to identify which lean tools are of most widespread use in the process industry, as well as their associated benefits. The publications obtained from this research were subjected to a quantitative analysis, which revealed that 80% of the documents comprise articles from journals, while only 20% appeared in conference proceedings. Of these publications and articles, 44% were cases studies, 35% consisted of research and 21% corresponds to questionnaires. With regard to distribution by country, it was found that approximately 50% of the documents published were limited to only three countries– India, Malaysia and the United States of America. Regarding the sector of activity, this distribution allowed to observe that the metalworking sector is the most targeted, followed by the textile and automotive areas, with a total of 24, 10 and 10 publications, respectively. This analysis allowed one to establish that the most frequently implemented tool mentioned in the articles is VSM (Value Stream Mapping), with a percentage of 65%. This is followed by 5S, which is also of widespread use, representing 48%, when compared to the total number of publications collected in the Web of Science.